THE INFLUENCE OF THE IMPLEMENTATION OF OUTDOOR SOCIAL SCIENCE LEARNING ON LEARNING ACTIVENESS OF CLASS IV STUDENTS AT SDN 257 AKKALIBATUE IN LILIRIAJA SUB-DISTRICT OF SOPPPENG DISTRICT - ANDI ANNA TRIANA AR (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2018)
Abstract : The research aims to discover (i) the learning activeness of class IV students at SDN 257 Akkalibatue in Liliriaja Sub-district of Soppeng District before the implementation of Outdoor Social Science learning; (ii) the learning activeness of class IV students at          SDN 257 Akkalibatue in Liliriaja Sub-district of Soppeng District after the implementation of Outdoor Social Science learning; (iii) whether there is a difference of learning activeness of class IV students at SDN 257 Akkalibatue in Liliriaja Sub-district of Soppeng District before and after   the implementation of Outdoor Social Science learning.The research was pre-experiment research which employed pre-test post-test one group design. The populations of the  research were the students of class IV with the total of 61 students. The samples of the research were 41 student. The determination of experiment was conducted by using random sampling technique. To know about the result of this research, researcher used observation sheet and enquette instrument. Observation sheet used to know the implementation of outdoor learning education. The learning result was analized by using t-test with SPSS 23.0 for Windows application. Data analysis using descriptive analysis technique and inferential analysis that is requirement test (normality and homogeneity test) and hypothesis test (t-test).The results of the research reveal that (i) the learning activeness of class IV students at SDN 257 Akkalibatue in Liliriaja Sub-district of Soppeng  District in Social Science learning before the implementation of outdoor learning, generally is in low category (ii) the learning activeness of class IV students at SDN 257 Akkalibatue in Liliriaja Sub-district of Soppeng District in Social Science learning after the implementation of outdoor learning, generally is in high category (iii) there is a difference of students’ learning activeness before and after the implementation of outdoor learning in Social Science in class IV students at SDN 257 Akkalibatue in Liliriaja Sub-district of Soppeng District, namely the students’ learning activeness is higher after the implementation of Outdoors Social Science learning than before the implementation of Outdoors Social Science learning. Keyword: implementation of outdoors social science learning, learning activeness of students.